NO2 SEASONAL AND INTERANNUAL VARIABILITY IN UKRAINIAN INDUSTRIAL CITIES - Savenets, Mykhailo; Nadtochii, Liydmyla; Dvoretska, Iryna (GeoScience Engineering, 2018)
The paper aims to define the main features and principles of seasonal and interannual NO2 variations in Ukrainian industrial cities. Using ground-based measurements for the 15-year period, it shows weak NO2 seasonal variability that could intensify in case of three regularities. These regularities depend on the impact of natural conditions during anthropogenic emissions growth and redistribution between emission sources. Most industrial cities are characterized by positive trends even if stationary industrial emissions fall. NO2 interannual changes form under a variety of fluctuations. However, 6.2- and 9.3-year periods have the biggest impact and might be explained by low-frequent lunar tidal forces through its influence on meteorological conditions. Keywords: NO2 emissions, industrial cities, seasonal variability, interannual variability, trend https://doi.org/10.2478/gse-2018-0019